2011
DOI: 10.1099/vir.0.030593-0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of ten novel cutaneous human papillomaviruses from keratotic lesions of immunosuppressed patients

Abstract: Viral warts from immunosuppressed organ transplant recipients (OTR) persist over years and may progress into non-melanoma skin cancer. The types of human papillomaviruses (HPV) in such lesions are different from that seen in the general population. A subset of these lesions is not infected with the classical wart-associated HPV types. In order to gain a better understanding of the HPV types in those lesions, we isolated ten novel HPVs from persisting keratotic lesions of immunosuppressed OTRs by rolling circle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 38 publications
2
42
0
Order By: Relevance
“…In fact, the intratype heterogeneity of HPVs from the genera Betapapillomavirus and Gammapapillomavirus has remained basically unexplored, and there is currently a significant effort to characterize novel types from these genera (Bottalico et al, 2011; Kohler et al, 2011; Li et al, 2012). With implementation of Next-Gen sequencing (Barzon et al, 2011; Ekstrom et al, 2011), it is anticipated that there will be rapid advances in studying these genome variants (Bernard, 2013), particularly if associated with pathologic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the intratype heterogeneity of HPVs from the genera Betapapillomavirus and Gammapapillomavirus has remained basically unexplored, and there is currently a significant effort to characterize novel types from these genera (Bottalico et al, 2011; Kohler et al, 2011; Li et al, 2012). With implementation of Next-Gen sequencing (Barzon et al, 2011; Ekstrom et al, 2011), it is anticipated that there will be rapid advances in studying these genome variants (Bernard, 2013), particularly if associated with pathologic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The validity of this concept was extensively demonstrated for cutaneous beta and gamma human papillomaviruses (β and γ-HPVs) that are commonly present on the superficial layers of the skin in most individuals [3][5]. Indeed, in this setting, several studies have reported the genetic diversity of cutaneous human papillomaviruses using consensus PCR targeting L1 gene [6] or more recently through sequencing rolling circle products [7], [8]. Furthermore, functional metagenomic methods were recently applied to cutaneous samples and led to the description of new human virus species belonging to the Polyomaviridae family.…”
Section: Introductionmentioning
confidence: 99%
“…Their prevalence and natural history, for example acquisition soon after birth, reflects a commensalic interaction with the immunocompetent host [8][10]. Historically, several cutaneous papillomaviruses have been isolated from patients with the genetic disease epidermodysplasia verruciformis [11], [12], and from immunosuppressed patients [13], probably due to higher viral loads among these patient groups [14]. As a consequence of improved methods, several PVs have been characterized, and the number of HPV types of the γ-PV genus has been expanded from 16 HPV types in 2010 [7] to 62 representative HPV types in 2013 (retrieved from GenBank, September 2013).…”
Section: Introductionmentioning
confidence: 99%